(untitled) (Latakia University Journal -Biological Sciences Series, 2021)
We present in this research the most important results related to the total abundance as well as the abundance of various groups of zooplankton in the coastal area of ​​Burj Islam and its vertical changes up to 300m depth, during the research period extended between November 2011 to June 2019, and the sampling process was associated with the measurement of temperature and salinity. The results of the study showed significant temporal and spatial changes in the abundance of various groups of zooplankton in the studied area, where the total abundance of zooplankton ranged between 20 and 597 ind./m3, which is low abundance compared to other regions of the Syrian coast and the Mediterranean. Copepoda was in the first level in terms of its contribution to the total abundance of zooplankton and ranged between 61% to 98%, the mean of relative abundance of the other groups did not exceed 3.7% recorded by the group of Appendiculata, Hydrozoa, Thaliacea, Chaetognatha, Ostracoda, with mean of relative abundance 2.77 and 1.9 and 1.8 and 1.6%, respectively, and the mean of relative abundance for the remaining groups did not exceed 0.4%. In general, we have noticed a sharp decrease in the abundance of the various studied zooplankton groups, especially under the depth of 100 m, which is consistent with many studies that have taken place in the coastal waters of the Mediterranean. We have also noticed a great correlation for the abundance between Copepoda and a number of groups of zooplankton, which are: Appendiculata, Chaetognatha, Hydrozoa, Ostracoda and Thaliacea, where the value of (r) 0.9 and 0.83 0.82, 0.77, and 0.65, respectively.